Stale Prices and the Performance Evaluation of Mutual Funds - Qian, Meijun (Journal of Financial and Quantitative Analysis, 2011)
Abstract Staleness in measured prices imparts a positive statistical bias and a negative dilution effect on mutual fund performance. First, evaluating performance with nonsynchronous data generates a spurious component of alpha. Second, stale prices create arbitrage opportunities for high-frequency traders whose trades dilute the portfolio returns and hence fund performance. This paper introduces a model that evaluates fund performance while controlling directly for these biases. Empirical tests of the model show that alpha net of these biases is on average positive although not significant and about 40 basis points higher than alpha measured without controlling for the impacts of stale pricing. The difference between the net alpha and the measured alpha consists of 3 components: a statistical bias, the dilution effect of long-term fund flows, and the dilution effect of arbitrage flows. Whereas the former 2 components are small, the latter is large and widespread in the fund industry.